Drivers of Renewable Energy Consumption: The Roles of Economic Growth, Carbon Intensity, and Innovation (International Journal of Scientific Research in Science and Technology, 2025)
Purpose- Climate change prevention via aggressive objectives for reducing greenhouse gas emissions is now a top focus on the global, regional, and national levels. Increased reliance on renewable energy sources emerged as the answer to achieving ecumenical energy security and sustainability through carbon neutrality within the practical framework for ecumenical climate action. This would enable countries to reduce energy imports and reduce the use of fossil fuels. Methodology- This study uses an empirical analysis of a large panel of countries and five income-predicted subpanels over the 1995-2019 period to examine the heterogeneous effects of relevant economic and environmental driving factors for renewable energy consumption (REC) that emerge from current policy objectives (GDP per capita, carbon intensity, and research and development). Findings- At the global level, CO2 intensity has a moderating influence on REC, and this link is stronger for low-income and very high-income nations. Additionally, when GDP per capita exceeds the 5000 USD mark, it encourages the use of renewable energy, however in nations with very high incomes, research and development play a significant role in increasing the consumption of renewable energy. Therefore, in order to create effective and consistent regulations, policymakers must take into account the variability of the REC drivers. Originality-Effect of Renewable Energy Consumption, i.e., non- financial indicator, on GDP per capita which is financial indicator.
Keywords: Renewable Energy Consumption; Carbon Intensity; GDP per Capita